1986
DOI: 10.1055/s-2007-1003576
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Glycoprotein and Collagenous Components of the Basement Membrane: Studies with Urokinase-Type Plasminogen Activator, α-Thrombin, and Plasmin

Abstract: Penetration of the basement membrane takes place at several stages of tumor invasion and meta stasis and appears to involve a variety of degradative proteolytic enzymes directly or indirectly under the regulation of malignant cells. 1 ' 2 ' 4 We have therefore evaluated the role of the neutral serine proteases: urokinase (plasminogen activator), α-thrombin, and plasmin in the degradation of intact basement membrane (BM) and BM components. 3 ' 5 ' 7 Homogeneously purified enzymes were incubated with isolated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…These results indicate that bestatin inhibited the conversion of latent forms of collagenase to the active forms, thus suggesting that plasma membrane aminopeptidases may be involved in the activation mechanism of type IV collagenase as well as the other matrix proteinases such as plasmin or stromelysin. Plasmin has long been known to directly degrade basement membrane components [37] and to activate the latent type IV collagenase produced by the tumor cells [52]. Bestatin only slightly inhibited plasmin activity of the tumor cells against Boc-Val-Leu-Lys-MCA, but this slight effect was not significant (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that bestatin inhibited the conversion of latent forms of collagenase to the active forms, thus suggesting that plasma membrane aminopeptidases may be involved in the activation mechanism of type IV collagenase as well as the other matrix proteinases such as plasmin or stromelysin. Plasmin has long been known to directly degrade basement membrane components [37] and to activate the latent type IV collagenase produced by the tumor cells [52]. Bestatin only slightly inhibited plasmin activity of the tumor cells against Boc-Val-Leu-Lys-MCA, but this slight effect was not significant (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained using the inhibitors of serine proteases and collagenases indicate that both classes of enzymes are necessary for the tumor cells to invade the basement membrane structures (Tables2 and 3). The plasmin generated from plasminogen by plasminogen activator could directly degrade basement membrane components [37,38] or activate the latent collagenase produced by the tumor cells [39]. We therefore examined the effect of bestatin on the plasmin activity of SN12M cells using two synthetic substrates (Table 4) and, unexpectedly, slightly increased SN12M cell degradation of Boc-Glu-Lys-Lys-MCA.…”
Section: Effect Of Bestatin On Aminopeptidase and Plasmin Activities mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 This enyzme degrades collagen type IV, which is a major part of the basement membrane. 12,13 This tumor cell surface-associated proteolysis is the prerequisite for the detachment of tumor cells from their surrounding tissue, which then might lead to tumor cell invasion and metastasis. Tumor cells may also synthesize the plasminogen activator inhibitor type 1 (PAI-1), which blocks the enzymatic activity of u-PA and tissue type plasminogen activator (t-PA).…”
mentioning
confidence: 99%
“…Previous reports suggested that ENO1 acts as a PLG receptor and concentrates PLG in the pericellular region of tumours and activated immune cells [18][19][20][21][22]. PL is a serine protease that degrades extracellular matrix and TJ proteins [28][29][30][31][32]. Based on these observations, we speculated that ENO1 in keratinocytes may act as a PLG receptor and may cause TJ barrier dysfunction by promoting PL-mediated disruption of cell-cell junctions, as observed in tumour and activated immune cells.…”
Section: Discussionmentioning
confidence: 70%